DESKTOP-BASED CASH INFORMATION SYSTEM FOR ENGGAL PINTU WORKSHOP - Putra, Candra Basroni; Sari, Gema Ika; Tresnawati, Shandy (Yayasan Education and Social Center, 2025)
The study is to examine, formulate, execute, and evaluate the accounting information system for cash receipts and disbursements at Bengkel Enggal Pintu. The study's approach is descriptive-analytical, using tools such as observation, interviews, and literature reviews. The design technique employed in this study is the waterfall model, which has phases for system design, need analysis, code development, program testing, and system implementation. The SDLC (System Development Life Cycle) strategy is utilized to design the system. This research included observation, interviews, and literature reviews as data collection methods. The PIECES approach is used to do the analysis. The cash receipts and expenditures information system at Bengkel Enggal Pintu was made using software that makes it easy for users to enter data. The author used Visual Studio 2022 for programming, MySQL for the database, and Crystal Reports for information reporting. The User Acceptance Test (UAT) is used to test the system utilizing black-box testing methods. This system may help with data entry, generate reports on cash collections and expenses, and support other purposes, while ensuring data accuracy and completeness.